The Affective Dimension of Direction and Its Effects on the Conformation of Groups in Contemporary Argentinean Theatre - Marin, Fwala-lo (2024)
This work studies the affective dimension on group processes of artistic creation and analyses, particularly, the case of Argentine independent theatre groups in the city of Córdoba. The study –whose methodology included ethnographic interviews and discourse analysis–is based on the question regarding the way in which groupalities are formed and the role played by theatre direction in them. The objective of this paper is to understand how affects contribute to the formation of groups with artistic creationpurposes. For that, I first recall my conceptualization, which is based on groupality. Secondly, I review theoretical contributions from Sara Ahmed and others in order to analyse the relationships between groups and affects. Lastly, I systematise four affective dimensions experienced by theatre direction, which intervene in the conformation of theatrical groups. The conclusion of this paper values the emotional dimension as a power for the artistic work itself.